If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + w)(5w + 2) = 0 Reorder the terms: (6 + w)(2 + 5w) = 0 Multiply (6 + w) * (2 + 5w) (6(2 + 5w) + w(2 + 5w)) = 0 ((2 * 6 + 5w * 6) + w(2 + 5w)) = 0 ((12 + 30w) + w(2 + 5w)) = 0 (12 + 30w + (2 * w + 5w * w)) = 0 (12 + 30w + (2w + 5w2)) = 0 Combine like terms: 30w + 2w = 32w (12 + 32w + 5w2) = 0 Solving 12 + 32w + 5w2 = 0 Solving for variable 'w'. Factor a trinomial. (6 + w)(2 + 5w) = 0Subproblem 1
Set the factor '(6 + w)' equal to zero and attempt to solve: Simplifying 6 + w = 0 Solving 6 + w = 0 Move all terms containing w to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + w = 0 + -6 Combine like terms: 6 + -6 = 0 0 + w = 0 + -6 w = 0 + -6 Combine like terms: 0 + -6 = -6 w = -6 Simplifying w = -6Subproblem 2
Set the factor '(2 + 5w)' equal to zero and attempt to solve: Simplifying 2 + 5w = 0 Solving 2 + 5w = 0 Move all terms containing w to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5w = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 5w = 0 + -2 5w = 0 + -2 Combine like terms: 0 + -2 = -2 5w = -2 Divide each side by '5'. w = -0.4 Simplifying w = -0.4Solution
w = {-6, -0.4}
| x^4-2x^4-2x^3+2x-1=0 | | 4x-4+2x+8= | | (6x+5)= | | 8x+5(x+3)-8= | | 13x+13y=720 | | 14y=13(y+16) | | 13x+18y=720 | | 13x+17y=720 | | 13x+16y=720 | | 7(14w)= | | 13[y-4]-3[y-9]-5[y+4]=0 | | 9(3x+2)=261 | | 12(4z+2)-1= | | 8(x+1)=15 | | 9n+7=79 | | 3n+20=30 | | 7x+6x=55 | | (D^4+2D^3-3D^2)y=3e^2x+4sinx | | x^2-5=8 | | -5+8=m-8 | | x(y^2-z^2)p+y(z^2-x^2)=z(x^2-y^2) | | -5(x+5)+11x= | | (1-x)ydx+(1+y)xdy=0 | | Y+4=-2+9 | | y^2dx+(xy+x^2)dy=0 | | -50=25y | | y=(1+p)x+p^2 | | 7(y-7)= | | p+q=z | | p^2-2p-3=0 | | 4x^2-25x+21=-9x+6 | | x^4-48x^2-49=0 |